6x^{2 }+ 15x -9
Hi Susan;
6x^{2} + 15x -9
3(2x^{2}+5x-3)
We can set this equal to zero...
3(2x^{2}+5x-3)=0
The parenthetical equation must equal zero. Therefore, we can eliminate the 3...
2x^{2}+5x-3=0
For the FOIL...
FIRST must be (2x)(x)=2x^{2}
OUTER and INNER must add-up to 5x.
LAST must be (3)(1) or (1)(3) and either number must be negative to produce -3.
(2x-1)(x+3)
Let's FOIL...
FIRST...(2x)(x)=2x^{2}
OUTER...(2x)(3)=6x
INNER...(-1)(x)=-1x=-x
LAST...(-1)(3)=-3
2x^{2}+6x-x-3
2x^{2}+5x-3
(2x-1)(x+3)=0
Either or both parenthetical equations must equal zero...
2x-1=0
2x=1
x=1/2
x+3=0
x=-3